2000
DOI: 10.1046/j.1440-1819.2000.00772.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect on electroencephalogram of chewing flavored gum

Abstract: The objective of the present study was to evaluate the effect on the electroencephalogram (EEG) of a chewing gum with and without our prepared new flavor. Electroencephalograms were obtained after the following three tests: chewing pure gumbase with sucrose (standard gumbase), chewing flavored standard gum and the inhalation of flavored aromatic oil. As the control, we used the pre-stimulus control EEG record without a stimulus. We examined the relationship between the pre-stimulus control record and the post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 26 publications
1
32
1
Order By: Relevance
“…Based on this, the authors proposed the enhancement of 8-10 Hz neuronal oscillations as an electrophysiological marker of thirst-quenching, viewed as a reward response in relation to motivation. Similar changes in functional state of the resting brain have been reported in the alpha (8-12 Hz) and beta (13-30 Hz) bands after consumption of confectionery products with refreshing properties (Morinushi, Masumoto, Kawasaki, & Takigawa, 2000). These changes were obtained after chewing a flavored gum; the major constituents of which were aromatic oils with cooling (spearmint) and sour (lemon balm) properties.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Based on this, the authors proposed the enhancement of 8-10 Hz neuronal oscillations as an electrophysiological marker of thirst-quenching, viewed as a reward response in relation to motivation. Similar changes in functional state of the resting brain have been reported in the alpha (8-12 Hz) and beta (13-30 Hz) bands after consumption of confectionery products with refreshing properties (Morinushi, Masumoto, Kawasaki, & Takigawa, 2000). These changes were obtained after chewing a flavored gum; the major constituents of which were aromatic oils with cooling (spearmint) and sour (lemon balm) properties.…”
Section: Introductionsupporting
confidence: 69%
“…Faster oscillations, such as those in the beta range, seem to contribute to sensorymotor coordination during information processing. From these, the enhancement of cortical oscillations obtained after water (Hallschmid et al, 2002) and chewing-gum (Morinushi et al, 2000) consumption may reflect an improvement of physiological resources for optimal task performance. However, in the absence of cognitive assessment, changes in brain oscillatory activity should be interpreted with caution.…”
Section: Introductionmentioning
confidence: 93%
“…Although the precise mechanism(s) underpinning these effects is unclear, Scholey et al (2009) suggest that the act of chewing flavourless material (Tahara, Sakurai, Ando, Shimada, Miura, and Saito, 2007) and flavoured gum (Morinushi, Masumoto, Kawasaki, and Takigawa, 2000) each have distinct effects on stress and mood.…”
Section: Introductionmentioning
confidence: 99%
“…If the direction and magnitude of force are changed, the arrangement and pattern of bony trabeculae are also changed. This causes changes in bone infiltration and resorption processes, and a change in skeletal appearance 6) . Young people in our modern times prefer an oval face that has a large angle of the mandibular angle area.…”
Section: Discussionmentioning
confidence: 99%
“…There was also a study on using electromyography to show the influence of chewing gum on various masticatory muscles, and, based on a study using gum, Karkazis and Kossioni 5) reported that the food properties infl uenced electromyogram during mastication, and that controlling the mastication rate could control the variation in food hardness. Also, in studies on the refreshing effect of chewing gum using a brainwave test, Morinushi et al 6) and Kim 13) found that chewing gum without spices increased al pha and beta waves by, and with spices added to gum, theta waves increased additionally. Also, there was a study reported that chewing gum increased bone marrow density in the mandibular angle and so could be helpful in preventing osteoporosis of the jawbone.…”
Section: Introductionmentioning
confidence: 99%